Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Tamu Pada Hotel Prime Plazal Kualanamu, Deli Serdang - Sander, Fedri Alex; Wahyudi, Dedi (CIVITAS: Jurnal Studi Manajemen, 2021)
This study aims to determine the effect of service quality and price on guest satisfaction at Hotel Prime Plaza Kualanamu. This research is a type of associative research that aims to analyze the influence between one variable and another. The population in this study were guests who stayed at the Prime Plaza Kualanamu Hotel in June-August 2020, as many as 4,368 guests. The sampling method used purposive sampling with a sample size of 175 respondents. Primary data were collected through distributing questionnaires and interviews, secondary data were collected through literature study. This research uses descriptive analysis techniques and linear regression analysis The results showed that simultaneously service quality and price had a positive and significant effect on guest satisfaction. With the value of the coefficient of determination can be seen from the Adjusted R Squarese of 0.951 which means that 95.1% of guest satisfaction variables can be explained by service quality and price. Meanwhile, the other 4.9% difference is influenced or explained by other variables not included in this study.